2016
DOI: 10.1159/000445561
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Combined Therapy with Hyperbaric Oxygen and Diltiazem Pretreatment on Myocardial Ischemia-Reperfusion Injury in Rats

Abstract: Background/Aims: In this study, we examined whether the combination of hyperbaric oxygen (HBO) and diltiazem therapy provided a cardioprotective effect on myocardial ischemia-reperfusion injury (MIRI) rat model. Methods: Sixty healthy Sprague-Dawley rats were randomly divided into sham, IR, diltiazem (5 mg/kg), HBO (0.25 MPa, 60 min) and combination therapy (HBO plus diltiazem) groups. MIRI model was established by ligating the left anterior descending for 30 min, followed by 60 min of reperfusion. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…In addition, recent research found that stronger protective effect of combined treatment of hyperbaric oxygen and diltiazem against cardiac I/R injury [22]. Thus, combined treatment with different intervention drug combination could better protect against I/R injury.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, recent research found that stronger protective effect of combined treatment of hyperbaric oxygen and diltiazem against cardiac I/R injury [22]. Thus, combined treatment with different intervention drug combination could better protect against I/R injury.…”
Section: Discussionmentioning
confidence: 98%
“…The myocardial tissue samples were isolated, fixed in 4% paraformaldehyde, embedded in paraffin, and cut into 5 um sections, according to routine histology procedures [4,23]. Next, sections were stained with hematoxylin and eosin (H&E) and examined by light microscopy at 400× magnification.…”
Section: Histopathological Examination Of Myocardial Tissuementioning
confidence: 99%
“…Myocardium undergoing ischemic injury followed by re-establishment of the blood supply generate superabundant oxygen free radicals, triggering oxidative stress, aggravating MIRI, and eventually resulting in mitochondrial dysfunction, cell damage, apoptosis, and necrosis [4]. The bioactive gas, NO, has pro-survival effects that can relieve myocardial I/R injury by scavenging oxygen free radicals, reducing thrombus formation caused by platelet activation, and regulating leukocyte mediated inflammation [26,27].…”
Section: Down-regulation Of Cd47 Attenuates I/r Induced Oxidative Strmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration of the coronary blood flow (reperfusion) is essential for the salvage of the ischemic heart, however, reperfusion itself may lead to lethal myocardium injury [1, 2], termed myocardial ischemia reperfusion (I/R) injury. Brief episodes of ischemia and reperfusion applied either before (ischemic preconditioning) or after (ischemic postconditioning) prolonged ischemia protects the hearts against myocardial I/R in non-diabetes.…”
Section: Introductionmentioning
confidence: 99%